Inovasi Media Pembelajaran Digital Scanproedu dalam Materi Teks Prosedur pada Siswa Kelas VII SMP Negeri 5 Pamekasan - Ayuni, Silviana Qurrotul; Alatas, Mochamad Arifin (Universitas Sebelas Maret, 2025)
The transformation of 21st-century learning demands contextual media innovations that are adaptive to the characteristics of digital native students. This study aims to describe the implementation of the Scanproedu digital learning media based on QR Code in procedural text material for seventh-grade students at SMP Negeri 5 Pamekasan. The research involved 30 students, with data collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that Scanproedu successfully improved students’ understanding of text structure, language use, and creativity in composing procedural texts. Most students (66.7%) met all three assessment aspects optimally. This media also fostered active participation, independent learning, and collaboration. Both teachers and students responded positively to the media’s ease of access and relevance to their digital habits. Technical obstacles such as limited device availability were overcome through group work strategies and the use of school Wi-Fi. These findings affirm that simple QR Code-based media like Scanproedu are effective in creating contextual and meaningful learning experiences. Further research is recommended to explore its application at different educational levels and in other types of texts or subjects.Transformasi pembelajaran abad ke-21 menuntut inovasi media yang kontekstual dan adaptif terhadap karakteristik siswa digital native. Penelitian ini bertujuan untuk mendeskripsikan penerapan media pembelajaran digital Scanproedu berbasis QR Code dalam materi teks prosedur pada siswa kelas VII SMP Negeri 5 Pamekasan. Subjek penelitian berjumlah 30 siswa, dengan data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa Scanproedu mampu meningkatkan pemahaman struktur teks, penggunaan kebahasaan, serta kreativitas siswa dalam menyusun teks prosedur. Sebagian besar siswa (66,7%) memenuhi ketiga aspek penilaian secara optimal. Media ini juga mendorong keterlibatan aktif, kemandirian belajar, dan kolaborasi. Guru dan siswa memberikan respons positif terhadap kemudahan akses dan relevansi media dengan kehidupan digital mereka. Kendala teknis seperti keterbatasan perangkat diatasi melalui strategi kerja kelompok dan pemanfaatan Wi-Fi sekolah. Temuan ini menegaskan bahwa media sederhana berbasis QR Code seperti Scanproedu efektif dalam membangun pengalaman belajar yang kontekstual dan bermakna. Penelitian selanjutnya disarankan untuk menguji penerapan media ini di jenjang pendidikan yang berbeda serta memperluas integrasinya pada jenis teks atau mata pelajaran lain.